Journal History of Latin American Education, leader in the historical–educational research eading educational research 1998-2013 - Arango, Diana Elvira Soto; Villate, Sandra Liliana Bernal (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
The purpose of this paper is to take a stock and a foresight of the Journal History of Latin American Education, from the editorial work during its 15 years of existence, it has highlighted the conditions of production, distribution, reception and searching, from a thematic analysis in the Latin American dimension of this publication. In its quality of pioneering and the one in its genre, RHELA is a scientific publication and it is a way of expression of the Society of History of the Latin-American Education – SHELA of the Doctorate in Sciences of the Education and of the research teams History and Futurology of the Latin-American University – HISULA and The Enlightenment in Colonial America – ILAC. The magazine is directed to researchers in the field of the history of the Latin-American Education, to sociologists, educators, political experts, and professionals involved in the field of social sciences, humanities and education. It is managed to hold support to the academic researchers. It has presented academic research impact by being a means of consultation referenced. It catalogs in international Índex is Ranked in Publindex - Colciencias in category ‘B’ and is published in physical and electronic means RUDECOLOMBIA website.